Implementasi Penilaian Pembelajaran Kurikulum 2013 dalam Meningkatkan Partisipasi Aktif Siswa di Sekolah Dasar - Rudini, Moh.; Khasanah, Alif (Pengembangan Pendidikan dan Pembelajaran Sekolah Dasar, 2022)
This study aims to(1) determine the implementation of the 2013 curriculum learning assessment in increasing the active participation of SDN 1 Buga students, (2) determine to know the inhibiting factors and supporting factors for the 2013 curriculum learning assessment implementation. This type of research is descriptive qualitative. Data collection techniques used in the form of observation, interviews and documentation. Data analysis uses data reduction, data display, conclusion drawing and verification. The results showed that the implementation of the 2013 curriculum learning assessment in increasing the active participation of fourth grade students at SDN 1 Buga was well implemented. The inhibiting and supporting factors are the availability of learning facilities and infrastructure that can support the implementation of the learning process, which is very much needed